Leadership in Perspective: Nature, Challenges, and Future Directions - Romero, Junan N. (Future Science / FSH-PH Publications, 2025)
Leadership is considered as a complex, multifaceted process of influencing, guiding, and managing people towards achieving common goals. It is not about authority or positions, but it requires innate and developed characteristics rooted in social responsibility and emotional intelligence. Researchers agree that effective leadership empowers others, promotes collaboration, and adapts to the changing organizational landscape. Moreover, it aims to address the challenges and ensures inclusive progress. In this light, this paper delves into the nature, impact, and types of leadership – examining the strengths and weaknesses such as autocratic, democratic, transformational, transactional, servant, charismatic, laissez-faire, bureaucratic, and situational leadership. It also highlights how these styles are interconnected and can be applied simultaneously. Furthermore, the research emphasizes the future of leadership, pointing out that blending two or more styles can foster a more motivated and satisfied organizational membership. This paper also states that no singular leadership style is solely or universally effective in all situations. Instead, the integration of multiple leadership styles which is coined as full-range or hybrid leadership, offering a more responsive, inclusive, and flexible workplace. The insights can serve as important framework for leadership development in numerous sectors most especially in education and governance.